Treatment and recycling of garment washing wastewater. Issue 1 (December 2015) - Du, X.; Qiu, X.; Zhang, Y.; Ni, J.
Abstract : Garment washing becomes more and more popular in recent two decades, while the investigation of its water reclamation was rare. Membrane bioreactors (MBRs) become an increasingly used technology in wastewater treatment because of their unique advantages like controlled biomass retention, good effluent quality, and decreased footprint. The auxiliaries in garment washing, especially silicate and silicone oil, could cause catastrophic membrane fouling. Coagulation as pretreatment of garment washing wastewater before membrane separation is necessary. Hydrolysis–acidification enhances the biodegradability for chemical oxygen demand (COD) removal in MBR. Subsequent nanofiltration (NF) produces better water quality with lower hardness, COD and conductivity. Membrane bioreactor effluent is proved to be sufficient for garment washing with the same quality as fresh water.